PROGRAM INTERVENSI KEMANUSIAAN BAGI PEMBINAAN NARAPIDANA - Rifai, Mochamad (JURNAL SOSIOLOGI, 2013)
This paper This paper reviews briefly about the need for humanitarian intervention programs for training inmates. The limit in this paper include: correctional policy (Correctional policy); effectiveness of intervention programs; and intervention programs (humanity) are effective.